Bioactivity of extracts of Centaurea polyclada dc. (Asteraceae) - Granger Melanie; Samson Emilie; Sauvage Severine; Majumdar Anisha; Nigam Poonam; Nahar Lutfun; Celik Sezgin; Sarker Satyajit D. (Archives of Biological Sciences, 2009)
The free radical-scavenging property, antibacterial activity, and brine shrimp toxicity of n-hexane, dichloromethane (DCM), and methanol (MeOH) extracts of Centaurea polyclada, an endemic Turkish species, were assessed using the 2,2-diphenyl-1-picryl-hydrazyl (DPPH) assay, the resazurin microtiter plate-based assay, and the brine shrimp lethality assay, respectively. The DCM and MeOH extracts of C. polyclada exhibited free radical-scavenging ability with RC50 values 1.17 and 0.015 mg/mL, respectively. Among solid-phase extraction fractions of the MeOH extract, the fraction eluted with 60% MeOH in water demonstrated the highest level of free radical-scavenging activity (RC50 = 0.016 mg/mL). Only the DCM extract showed considerable antibacterial activity against all nine test strains except Escherichia coli, with MIC ranging from 1.25 to 2.50 mg/mL. This antibacterial activity pattern was also observed with solid-phase extraction fractions of the DCM extract with varied potencies. None of the extracts showed any significant toxicity towards brine shrimps (LD50 = >1.00 mg/mL).